Susceptibility of brain to aerobic, anaerobic, and fungal organisms. - Costello, G T (1983)
The utility of an experimental animal model is dependent on its ability to simulate the actual clinical situation. With a stereotaxic injection procedure, the susceptibility of rat brain to the spectrum of organisms commonly associated with human brain abscess was determined. Two strains of Escherichia coli were more infective than Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus pyogenes. Even between the E. coli strains it was possible to document significant differences in degree of infectivity. The E. coli strain with the K-1 capsular polysaccharide was significantly more infective than the E. coli strain without the capsular polysaccharide. The brain was also susceptible to Candida albicans, but at a level higher than any of the aerobic bacteria examined. Brain infection could not be created when microaerophilic or obligately anaerobic organisms alone were injected.